Novel self-assembled 3D flower-like magnesium hydroxide coated granular polyurethane: Implication of its potential application for the removal of heavy metals - Vafaeifard, Mohsen; Ibrahim, Shaliza; Wong, Kien Tiek; Pasbakhsh, Pooria; Pichiah, Saravanan; Choi, Jaeyoung; Yoon, Yeomin; Jang, Min (Elsevier, 2019)
Novel nanostructured three-dimensional flowerlike Mg(OH) 2 -incorporated granular polyurethane (designated as gPU-FMH) was prepared using a simple hydrothermal method, for which commercial MgO, water, and granular polyurethane (gPU) were applied. Interestingly, it is found that gPU and the hydrothermal process are the key factors for the assembly of the flowerlike structures of the Mg(OH) 2 , as its hexagonal nanosheet petals provide a high surface area. Temperature significantly controlled the morphologies of the flowerlike Mg(OH) 2 , and the granular gPU-FMH showed the superb adsorption capacities of 472, 1050, and 1293 mg g −1 (maximum adsorption capacities, q m , from Langmuir model) for Cu(II), Cd(II), and Pb(II), respectively. The proposed hypothesis for the synthesis of gPU-FMH and the removal mechanism of the heavy metals has been proved through various spectroscopic analyses. In the result of the continuous-flow column study, gPU-FMH showed a long breakthrough and a high removal capacity (184 mg g −1 ) of Cu(II). © 2018 Elsevier Ltd